IDENTIFICATION OF MEDICINAL PLANTS AND BENEFITS IN THE VILLAGE OF NEGERI LIMA, MALUKU DISTRICT - Nusaly, Windy Natalia; Watuguly, Theopilus Wilhelmus; Pattiasina, Eifan Boyke; Wael, Syahran (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2023)
Backgraound: Medicinal plants are the biodiversity that exists around us, both those that grow wild and those that are deliberately cultivated. For generations, plants have been used as medicinal plants. The largest part of medicinal raw materials derived from plants is still not cultivated, while opportunities for agribusiness have the potential to increase the opportunities and possibilities open for medicinal products. Methods: The aim of the research is to find out the types of medicinal plants and find out how the community perceives the benefits of medicinal plants in the village of Negeri Lima. Maluku. The material used in this research is a questionnaire or questionnaire. The research uses the Guttman scale by distributing questionnaires to respondents which are used to find scores, percent scores, total scores, and percent ideal scores, the results of which are converted into score interpretation criteria. Results: The research results showed that the criteria distributed to respondents were very good with the highest total score being 90% and the lowest being 10%. Conclusion: As a result of the identification carried out, 20 types of medicinal plants were identified which were spread across Negeri Lima Village, Central Maluku. Analysis of questionnaires distributed to the public to measure public perceptions by distributing questionnaires used the Guttman scale from question no. 1 - 5, it is known that the highest percentage is 90% and the lowest percentage is 10%. Meanwhile, the results of the analysis of attitude question items to measure public perception from question no. 6 - 10 has the highest percentage, namely 80% and the lowest percentage, namely 20%.